Vaccine effectiveness against COVID-19 hospitalisation in adults (≥ 20 years) during Omicron-dominant circulation: I-MOVE-COVID-19 and VEBIS SARI VE networks, Europe, 2021 to 2022 - Rose, Angela Mc; Nicolay, Nathalie; Sandonis Martín, Virginia; Mazagatos, Clara; Petrović, Goranka; Baruch, Joaquin; Denayer, Sarah; Seyler, Lucie; Domegan, Lisa; Launay, Odile; Machado, Ausenda; Burgui, Cristina; et al. (Euro surveillance, 2023)
IntroductionThe I-MOVE-COVID-19 and VEBIS hospital networks have been measuring COVID-19 vaccine effectiveness (VE) in participating European countries since early 2021.AimWe aimed to measure VE against PCR-confirmed SARS-CoV-2 in patients ≥ 20 years hospitalised with severe acute respiratory infection (SARI) from December 2021 to July 2022 (Omicron-dominant period).MethodsIn both networks, 46 hospitals (13 countries) follow a similar test-negative case-control protocol. We defined complete primary series vaccination (PSV) and first booster dose vaccination as last dose of either vaccine received ≥ 14 days before symptom onset (stratifying first booster into received < 150 and ≥ 150 days after last PSV dose). We measured VE overall, by vaccine category/product, age group and time since first mRNA booster dose, adjusting by site as a fixed effect, and by swab date, age, sex, and presence/absence of at least one commonly collected chronic condition.ResultsWe included 2,779 cases and 2,362 controls. The VE of all vaccine products combined against hospitalisation for laboratory-confirmed SARS-CoV-2 was 43% (95% CI: 29-54) for complete PSV (with last dose received ≥ 150 days before onset), while it was 59% (95% CI: 51-66) after addition of one booster dose. The VE was 85% (95% CI: 78-89), 70% (95% CI: 61-77) and 36% (95% CI: 17-51) for those with onset 14-59 days, 60-119 days and 120-179 days after booster vaccination, respectively.ConclusionsOur results suggest that, during the Omicron period, observed VE against SARI hospitalisation improved with first mRNA booster dose, particularly for those having symptom onset < 120 days after first booster dose.
Keywords: vaccine effectiveness; RNA, Messenger; omicron; hospitalizace; Europe; Adult; vakcíny proti COVID-19; pneumonie; dospělí; Pneumonia; SARS-CoV-2; účinnost vakcíny; Evropa; lidé; Humans; Hospitalization; hospital; COVID-19 Vaccines; Vaccine Efficacy; messenger RNA; COVID-19